Photochemistry, photophysics and nonlinear optical parameters of phenoxy and tert-butylphenoxy substituted indium(III) phthalocyanines - Chauke, Vongani; Durmuş, Mahmut; Nyokong, Tebello (Elsevier Science Sa, 2007)
This work hereby presents the syntheses, photochemistry and photophysics of octaphenoxy ((Cl)lnOPPc) and octakis(4-tert-butyl phenoxy)chloroindium ((Cl)InOTBPPc) phthalocyanines. Calculated nonlinear parameters of these complexes are compared with those of the corresponding GaPc derivatives and tetrasubstituted GaPc and InPc complexes. Fluorescence quantum yields do not vary much between (Cl)InOPPc and (Cl)InOTBPPc complexes in different solvents. High quantum yields of triplet state (phi(T) ranging from 0.70 to 0.91 in dimethysulphoxide, DMSO) and singlet oxygen generation (phi(Delta), ranging from 0.61 to 0.79 in DMSO) were obtained. Short triplet lifetimes 50 - 60 mu s were obtained in DMSO). The optical limiting threshold intensity (I-lim) for the InPc derivatives were calculated and compared with those of corresponding tetrasubstituted InPc and GaPc complexes. The latter were found to be better optical limiters. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: indium phthalocyanine; galium phthalocyanine; triplet quantum yield; triplet lifetime; fluorescence quantum yield; singlet oxygen quantum yield; nonlinear optical parameters